1997
DOI: 10.1074/jbc.272.41.25783
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Radiation-induced Apoptosis Is Mediated by Activation of CD-95 (Fas/APO-1)

Abstract: Exposure to ultraviolet light (UV) can induce apoptosis in mammalian cells. The mechanism by which UV radiation engages the suicide apparatus is unclear. Here we demonstrate that UV radiation can activate the Fas pathway via receptor aggregation and subsequent recruitment of the death adaptor molecule FADD/MORT1. UV radiation-induced apoptosis was inhibited by both a dominant negative version of FADD (FADD-DN) and the caspase inhibitor CrmA. Thus, activation of the Fas pathway represents a physiologic mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
233
4
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(257 citation statements)
references
References 11 publications
19
233
4
1
Order By: Relevance
“…Thus, in p53 null H1299 cells, the IRmediated apoptotic signals clearly di er from those of UV's in that they do not appear to engage the plasma membrane component involving FADD or the proximal caspases 8 and 10. Our results are consistent with those reported recently by Datta et al (1997) and Rehemtulla et al (1997) that CrmA did not block IR-induced apoptosis. Using the caspase 3 knock-out cells, Woo et al (1998) have also recently reported that while UVinduced apoptosis was blunted in caspase 3 de®cient cells, IR-induced apoptosis was not.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Thus, in p53 null H1299 cells, the IRmediated apoptotic signals clearly di er from those of UV's in that they do not appear to engage the plasma membrane component involving FADD or the proximal caspases 8 and 10. Our results are consistent with those reported recently by Datta et al (1997) and Rehemtulla et al (1997) that CrmA did not block IR-induced apoptosis. Using the caspase 3 knock-out cells, Woo et al (1998) have also recently reported that while UVinduced apoptosis was blunted in caspase 3 de®cient cells, IR-induced apoptosis was not.…”
Section: Discussionsupporting
confidence: 94%
“…TNFR1 and Fas are the membrane death receptors that are known to relay apoptotic signals via FADD (reviewed by Nagata, 1997). UV-induced ligand independent aggregation-mediated activation of Fas has recently been reported (Rehemtulla et al, 1997;Aragane et al, 1998). In MCF-7 cells that express TNFR1 but do not express functional Fas (Keane et al, 1996), the ability of FADD-DN to partly inhibit UV-induced apoptosis, as we noted in the present study, highlights the individual contribution of TNFR1.…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, dysregulation of UV-induced apoptosis will affect the photocarcinogenic risk. Several ways exist to inhibit UV-induced apoptosis, e.g., by overexpressing heat shock (29) or antiapoptotic proteins (30,31), by disrupting p53 function (32), or by blocking death receptor activation (33,34). Because these approaches allow the survival of cells carrying DNA damage, they may give rise to mutations and skin cancer.…”
Section: Discussionmentioning
confidence: 99%
“…37 Previous work showed that exposure of cells to UVR results in an inhibition of global protein synthesis. 14,38,39 This observation leads to the question of why an additional regulatory mechanism, such as degradation of cIAP1 mRNA, would be employed by cells to silence the expression of target genes following UVR.…”
Section: Discussionmentioning
confidence: 99%